2018
DOI: 10.20527/bipf.v6i3.5436
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Problem Based Learning terhadap Higher Order Thinking Skills Peserta Didik

Abstract: Higher Order Thinking Skills (HOTS) sangat diperlukan oleh peserta didik guna meningkatkan kemampuannya dalam mengatasi masalah pembelajaran. Hasil observasi menunjukkan bahwa masih banyak peserta didik di SMA Negeri 1 Manokwari yang mengalami kesulitan dalam memahami konsep fisika yang menurut mereka rumit. Salah satu model pembelajaran yang dapat melatih kemampuan berpikir peserta didik atau HOTS melalui penyelesaian masalah yaitu Problem Based Learning (PBL). Tujuan penelitian ini adalah menganalisis apakah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 2 publications
2
12
0
8
Order By: Relevance
“…This could be seen from the increase in the average value of HOTS in the experimental class compared to the average value of the control class, as the effect of PBL application. The findings of this study were in accordance with the studies of Aryani [8], Fatimah [11], Herzon, Budijanto, Utomo [12], Jayanti [13], Marlina, Utaya, Yuliati [14], and Royantoro [2] which showed that the PBL learning model had a significant effect on the HOTS of students. However, the same results of this study were not in line with the research of Putri, Corebima, Mahanal [6] who concluded that there was no influence between PBL learning strategies on metacognitive skills of students with low academic abilities.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This could be seen from the increase in the average value of HOTS in the experimental class compared to the average value of the control class, as the effect of PBL application. The findings of this study were in accordance with the studies of Aryani [8], Fatimah [11], Herzon, Budijanto, Utomo [12], Jayanti [13], Marlina, Utaya, Yuliati [14], and Royantoro [2] which showed that the PBL learning model had a significant effect on the HOTS of students. However, the same results of this study were not in line with the research of Putri, Corebima, Mahanal [6] who concluded that there was no influence between PBL learning strategies on metacognitive skills of students with low academic abilities.…”
Section: Resultssupporting
confidence: 92%
“…The results of studies conducted at Junior Secondary Schools in Probolinggo Regency, part of East Java, showed that in teaching the social studies, teachers used conventional methods so that students could not able to think at high levels [1][2][3]. This was due to the teaching methods by the teachers did not encourage the students' learning motivation.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the PBL model directs the active role of self in solving problems it faces with its knowledge [1]. Therefore this model can improve students' critical thinking skills [2], encourage initiative in work, and can develop interpersonal relationships in their groups.…”
Section: Introductionmentioning
confidence: 91%
“…(2) research conducted by (Abdurrozak & Jayadinata, 2016), The result is that the problem-based learning model affects students' creative thinking skills. (3) research conducted by (Royantoro et al, 2018), the result is the problem-based learning model of students' high order thinking skills.…”
Section: Introductionmentioning
confidence: 99%